Theories and policies of macroeconomics - Wilkinson, Preston (Wilmington American Academic Publisher, 2024)
When we study economy at large, we use the term "macroeconomics". macroeconomics is concerned with the understanding of aggregate phenomena such as economic growth, business cycles, unemployment, inflation and international trade among others These topics are of particular relevance for the development and evaluation of economic policy. This book "Theories and Policies of macroeconomics" deals with balanced approach between theoretical and mathematical aspects of the subject has been adopted to ensure ease and clarity in leaning. The book brings classroom teaching directly to the student has been adopted to ensure ease and that it uses.
Keywords: Macoeconomics; Economic theories of devlopment & planning; Theory of applications of macroeconomics